Effects of enhanced external counterpulsation on exercise capacity and quality of life in patients with chronic heart failure: A meta-analysis. Issue 27 (9th July 2021) - Zhou, Zhao-Feng; Wang, Da-jie; Li, Xu-Mei; Zhang, Cheng-Lin; Wu, Chun-Yang
Abstract: Background: This meta-analysis aimed to synthesize randomized controlled trials to evaluate the effects of enhanced external counterpulsation (EECP) on exercise capacity and quality of life in patients with chronic heart failure (CHF). Methods: Both English and Chinese databases were searched from their inception to June 30, 2020 (PubMed, EMBASE, Cochrane Library, CINAHL (EBSCO), Web of Science for English publications and Chinese Biomedical Database, China National Knowledge Infrastructure, Wanfang Data for Chinese publication). Titles, abstracts, and full-text articles were screened against study inclusion criteria: randomized controlled trials studying EECP intervention for patients with CHF. The meta-analysis was conducted with Revman 5.3 or STATA 16.0. Results: Eight randomized controlled trials were included. EECP induced significant improvement in 6-min walking distance (WMD=84.79 m; 95% CI, 47.64 to 121.95; P < .00001). Moreover, EECP was beneficial for left ventricular ejection fraction (SMD = 0.64; 95% CI, 0.29 to 1.00; P = .0004), and N-terminal pro brain natriuretic peptide (SMD = −0.61; 95%CI, −1.20 to −0.01; P = 0.04).However, compared with the control groups, EECP did not significantly reduce the Minnesota Living with Heart Failure Questionnaire scores(WMD, −9.28; 95% CI, −19.30 to 0.75; P = 0.07). Conclusions: Despite heterogeneity and risk of bias, this meta-analysis confirms that EECP can improve exercise capacity in CHF patients, especially the elderly. However, the evidence that EECP improves the quality of life in patients with CHF is still insufficient. More and larger well-designed randomized controlled trials are still warranted. Registration information: PROSPERO registration no. CRD 42020188848.